How do children make sense of peace and war? An exploratory study through the drawings of Italian pupils with an indirect experience of the war in Ukraine - Cornaggia, Alessia; Bianco, Federica; Castelli, Ilaria (Ricerche di Psicologia - Open Access, 2025)
The indirect exposure to war could have an impact on children’s construction of meaning about peace and war. The study investigates Italian children’s representations of peace and war by observing the contents and expressive connotations of their drawings, and the possible influences of the conflict in Ukraine. Drawings of peace and war of 38 children (M = 9.43, SD = 1.47) were collected in Italy in the Spring of 2022 after the beginning of the war in Ukraine. Parents answered a socio-demographical questionnaire, including information about family indirect experience of war. According to previous literature, peace images resulted as positive actions or absence of war, and war images are typical objects and activities of war. In contrast to the negative connotation of war drawings, peace drawings were more colored and convey a positive expressivity. The majority of children began by representing peace and included few people in both drawings. The frequencies of references to the war in Ukraine are not high, even if the majority of children talked about war with their parents after the beginning of the war in Ukraine. Educational implications of understanding the representations of peace and war in children with indirect exposure to conflicts are discussed.